The Analysis of Scientific Practices Skills of Students in Basic Physics Practicum: Authentic Assessment - Nurfadilah Nurfadilah; Riskawati Riskawati; Fani Fani; Amalia Ahmad; Nur Fadilah Nur Fadilah (Jurnal Ilmiah Pendidikan Fisika, 2023)
Assessment of practicum activities must encompass all aspects of scientific practices. Observations in this research indicate that the assessment utilized by the Physics Education Study Program at Universitas Muhammadiyah Makassar for practicum activities is an Authentic Assessment consisting of three assessment components: response, practicum activities, and report. This assessment is the result of development by one of the lecturers who taught courses integrated with practicum activities in 2015, and its implementation began in 2016. Using authentic assessment instruments in the form of worksheet, this study aims to assess the scientific practice skills of students enrolled in Basic Physics practicum. This research employed quantitative descriptive research. Thirteen first-semester students in the academic year 2022/2023 participated as the research subject. The results demonstrate that the assessment conducted using authentic assessment in practicum activities did not encompass all indicators of scientific practice skills. The authentic assessment did not include three of the eight indicators of scientific practice skills, namely the ability to ask questions, develop and use a model, and discover, evaluate, and communicate data findings. Therefore, it is necessary to utilize specialized assessment to measure the effectiveness of scientific practices, such as scientific practices assessment instruments.